2019
DOI: 10.1111/psyp.13499
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometric investigation into the speed‐accuracy trade‐off in a visuo‐motor aiming task

Abstract: Convergent lines of evidence suggest that fluctuations in the size of the pupil may be associated with the trade‐off between the speed (adrenergic, sympathetic) and accuracy (cholinergic, parasympathetic) of behavior across a variety of task contexts. Here, we explored whether pupil size was related to this trade‐off during a visuospatial motor aiming task. Participants were shown visual targets at random locations on a screen and were instructed and incentivized to move a computer mouse‐controlled cursor to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 65 publications
7
15
0
Order By: Relevance
“…To assess whether this manipulation had a physiological proxy consistent with a manipulation of the participant's SP state, we quantified pupil diameter. Our analyses reported increases of pupil diameter with SP, consistently with previously reported covariates of internal drives [26][27][28][29][30] . For this analysis, we pulled together the data across both control regimes (stop-in & cross-over), z-scored each participant's pupil size recording, and averaged across two 1s motion-free intervals of interest (FIG 4A).…”
Section: Ocular Correlates Of Social Pressuresupporting
confidence: 90%
“…To assess whether this manipulation had a physiological proxy consistent with a manipulation of the participant's SP state, we quantified pupil diameter. Our analyses reported increases of pupil diameter with SP, consistently with previously reported covariates of internal drives [26][27][28][29][30] . For this analysis, we pulled together the data across both control regimes (stop-in & cross-over), z-scored each participant's pupil size recording, and averaged across two 1s motion-free intervals of interest (FIG 4A).…”
Section: Ocular Correlates Of Social Pressuresupporting
confidence: 90%
“…In response to relevant events, phasic firing of the LC occurs and results in transient pupil dilations. During (tonic) periods of exploration, task disengagement and the exploration of new sources of reward is facilitated, and baseline firing of the LC and pupil size are elevated [26][27][28]. This contrast concurs with the rest-and-digest versus fight/flight function of the parasympathetic versus sympathetic components of the autonomous, PNS, respectively [2,29].…”
Section: Intermediate-level Responsesmentioning
confidence: 94%
“…In addition to saliency (conspicuity), pupil responses thus also depend on the timing of the onset of processing of sensory events. The pupil as a tool to mark the order of processes has been demonstrated beyond sensory tasks, including the highlighting of object detection versus subsequent identification phases [92] and ballistic versus subsequent error-correction phases of motor coordination [27].…”
Section: Higher-level Responses Modulated By Executive Functionsmentioning
confidence: 99%
“…Additionally, the SC is involved in transient changes in pupil size 18 . It has been suggested that the pupil's response to sensory events plays an important role in orienting responses as it is modulated by saliency, focused spatial attention, and motor coordination [19][20][21] .…”
mentioning
confidence: 99%